Telaah Pemikiran Tasawuf Nursamad Kamba dalam buku Mencintai Allah Secara Merdeka - Syarief Sultana, Muhammad (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2024)
Study of Nursamad Kamba's Sufism Thought in the book Loving Allah Independently. This research was conducted to find out how Nursamad Kamba's Sufism Thought in the book Loving Allah Merdeka. This study uses a qualitative method by analyzing the literature review. This type of research has data sources that are processed through literature related to the object. Based on the research conducted, the results obtained from the following conclusions: Buya Kamba considers that the path of Sufism is a way to transform human character. Buya Kamba wants to position and understand Sufism as a framework for building human psychology that can lead to positive self-character. In relation to the Novel Loving Allah Merdeka. Buya Kamba explains and invites readers (humans) to understand and recognize God, starting with knowing oneself and what it means to love God freely.